Another Look at Job Design with Conflicting Tasks1. (26th June 2018) - Pi, Jiancai
Abstract : This paper provides another look at job design with conflicting tasks. In a two‐stage moral hazard framework with risk‐neutral agents and limited liability, we study externalities that the first‐stage outcome has on the second‐stage success probability. We focus on outcome externalities with regard to the fixed (i.e. effort independent) part of the second‐stage success probability. Our results differ from the case studied by Schmitz (2013a ), who considers outcome externalities with regard to the marginal second‐stage success probability.